Psychoeducational Intervention for Symptom Management of Fatigue, Pain, and Sleep Disturbance Cluster Among Cancer Patients: A Pilot Quasi-Experimental Study - Nguyen, Ly Thuy; Alexander, Kimberly; Yates, Patsy (Journal of pain and symptom management, 2018)
To assess the feasibility of conducting a trial of a psychoeducational intervention involving the provision of tailored information and coaching to improve management of a cancer-related symptom cluster (fatigue, pain, and sleep disturbance) and reduce symptom cluster impacts on patient health outcomes in the Vietnamese context and to undertake a preliminary evaluation of the intervention. A parallel-group single-blind pilot quasi-experimental trial was conducted with 102 cancer patients in one Vietnamese hospital. The intervention group received one face-to-face session and two phone sessions delivered by a nurse one week apart, and the comparison group received usual care. Patient outcomes were measured at baseline before the chemotherapy cycle and immediately preceding the next chemotherapy cycle. Separate linear mixed models were used to evaluate the impact of the intervention on total symptom cluster severity, symptom scores, functional status, depressive symptoms, and health-related quality of life. The study design was feasible with a recruitment rate of 22.6% and attrition rate of 9.8%. Compared to the control group, the intervention group showed a significant reduction in symptom cluster severity, fatigue severity, fatigue interference, sleep disturbance, depression, and anxiety. Significant differences were not observed for pain severity, pain interference, functional status, and health-related quality of life. The intervention was acceptable to the study population, with a high attendance rate of 78% and adherence rate of 95.7%. On the basis of the present study findings, future randomized controlled trials are needed to test the effectiveness of a symptom cluster psychoeducational intervention in Vietnam.